Factors Influencing Students’ Entrepreneurial Intention In Kingdom Of Saudi Arabia: The Role Of Entrepreneurial Education And University Environment As The Mediator And Moderator - Alolaqi, Sultan Awad A (2024)
Entrepreneurship has been a key driver of the economy by creating innovation, jobs and a higher standard of living. An entrepreneurial mindset can play an immense role in meeting the goals of the government’s sustainable growth plans. By reviewing the reality of the unemployment problem among the youth, along with its risks and approaches to overcoming it, the role of entrepreneurial intention among young undergraduate students (currently enrolled on an entrepreneurship course) is to alleviate the severity of the unemployment problem in The Kingdom of Saudi Arabia. Considering the role of individual entrepreneurship awareness, this study suggests the conceptualization of the effective factors. Those factors include: individual entrepreneurial orientation (IEO) (Innovativeness, proactiveness and risk-taking), entrepreneurial social support (ESS) (Family support and peer-group support), the entrepreneurship education (EE), the entrepreneurial university environment (EUE) and the individual entrepreneurial intention (IEI). For the collection of the data, this study utilised the quantitative online-survey method with the convenience sampling technique. For fruitful insights, the current study analysed the data using the Statistical Package for the Social Sciences (SPSS), Smart-PLS Software and SPSS Software. The framework proposed in this theory is under the spectrum of Stimulus-Organism-Response S-O-R Theory. The overall findings of this research suggest recommendations to the policymakers and government bodies that in order to create xvii an environment of entrepreneurial education in universities, students’ entrepreneurial intention needs to be created and examines whether the proposed factors effect this intention.